2013
DOI: 10.4067/s0718-95162013005000049
|View full text |Cite
|
Sign up to set email alerts
|

The effects of phosphite on strawberry yield and fruit quality

Abstract: Phosphite (H 2 PO 3 -; Phi) has been shown to increase fruit quality and activate plant defense mechanisms in plants when provided in a nutrient state with sufficient phosphorous. In this study, five solutions containing different percentages of Phi (0, 20, 30, 40 and 50%) in Steiner's solution were evaluated during the flowering and fructification stages; the Steiner' s nutrient solution was kept al 50% during the flowering stage and at 75% from the beginning of the fructification stage on. The objective was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 26 publications
(29 reference statements)
2
16
0
2
Order By: Relevance
“…Potassium phosphite as a single treatment significantly increased the values of total yield and dry weight of yield (325.10 g) and (12.78 g), respectively using foliar application at C3 (0.2 ml plant -1 ), while with soil application increased the values of total yield and dry weight 301.21 g and 12.73 g, respectively at C2 (0.1 ml plant -1 ). The present results agree with those obtained by Gonzalez et al, (2010); Cicore et al, (2011); Silva et al, (2011); Monsalve et al , (2012); Pinto et al, (2013);Estrada-ortiz et al, (2013) who found that Phi increased total yield, fruit size, fresh & dry matter and number of fruit, these positive effect are due to activation the synthesis of antioxidant metabolites and internal hormonal and chemical changes by phi application. Also, Similar results were also concluded by Khalil et al ., (2011); Selim and Mosa, (2012); Patti et al, (2013); Suh et al, (2014); Diab et al, (2017); Farid et al, (2018) who found that FA increased the yield and all physical and chemical characteristics of fruits.…”
Section: Resultssupporting
confidence: 93%
“…Potassium phosphite as a single treatment significantly increased the values of total yield and dry weight of yield (325.10 g) and (12.78 g), respectively using foliar application at C3 (0.2 ml plant -1 ), while with soil application increased the values of total yield and dry weight 301.21 g and 12.73 g, respectively at C2 (0.1 ml plant -1 ). The present results agree with those obtained by Gonzalez et al, (2010); Cicore et al, (2011); Silva et al, (2011); Monsalve et al , (2012); Pinto et al, (2013);Estrada-ortiz et al, (2013) who found that Phi increased total yield, fruit size, fresh & dry matter and number of fruit, these positive effect are due to activation the synthesis of antioxidant metabolites and internal hormonal and chemical changes by phi application. Also, Similar results were also concluded by Khalil et al ., (2011); Selim and Mosa, (2012); Patti et al, (2013); Suh et al, (2014); Diab et al, (2017); Farid et al, (2018) who found that FA increased the yield and all physical and chemical characteristics of fruits.…”
Section: Resultssupporting
confidence: 93%
“…In maize, phosphites stimulated eliciting biochemical responses by increasing guaiacol peroxidase activity and lignin biosynthesis [27]. In strawberry phosphites were related to higher fruit quality and stimulation of defense mechanisms by increasing anthocyanin production [28].…”
Section: Resultsmentioning
confidence: 99%
“…Research suggests that foliar application of Phi has no effect on growth or yield and quality of the strawberry fruits in comparison with Pi fertilization (Moor et al ., ). However, other studies have indicated that phi improves fruit quality and plant defence mechanisms in strawberry cultivars (Estrada‐Ortiz et al ., , , ; Glinicki et al ., ). Studies have reported that the availability of Pi to plants is the key determinant for Phi toxicity.…”
Section: Biostimulatory Effects Of Phi On Plantsmentioning
confidence: 99%
“…(). It was further reported that the free amino acids and protein contents in leaves, sugar content (Estrada‐Ortiz et al ., ) and total anthocyanin content (Estrada‐Ortiz et al ., ) were increased in response to the application of Phi (Estrada‐Ortiz et al ., ).…”
Section: Biostimulatory Effects Of Phi On Plantsmentioning
confidence: 99%